Spatial-temporal evolution and influencing factors of tourism eco-efficiency in China’s Beijing-Tianjin-Hebei region - Li, Yunyan; Zhang, Ying (Frontiers in Environmental Science, 2022)
Tourism eco-efficiency is an important index to measure the sustainable development of the tourism industry. The super-SBM (slacked-based measure) model based on undesired output, geographical spatial analysis method, and panel Tobit regression model were used to explore the spatial-temporal evolution characteristics of tourism eco-efficiency and its influencing factors on 13 cities in China’s Beijing-Tianjin-Hebei region from 2010 to 2019. The results reveal that: (1) During the study period, high-efficiency cities were mainly in Beijing, Tianjin, and their surrounding areas, and the number of these cities did not change, whereas low-efficiency areas were farther away from central cities, and the number of these cities increased earlier but decreased later. (2) The tourism eco-efficiency in the Beijing-Tianjin-Hebei region exhibits significant positive spatial autocorrelation characteristics, and the driving effect of the spatial radiation of high-efficiency cities on low-efficiency cities in the urban agglomeration is more obvious. (3) The levels of economic development, tourism industry structure, urbanization, and technological progress have a greater impact on tourism ecological efficiency.